Strengthening the Authority of Financial Institutions in Preventing Money Laundering and Terrorism Financing in Indonesia to Improve the Effectiveness of the National Financial Supervisory System - Kurniawan, Aga; Herman, KMS (Asian Journal of Social and Humanities, 2025)
Transnational financial crimes that jeopardize national security and the stability of the financial system include money laundering and financing terrorism. Although Indonesia has a comprehensive legal framework, such as Law No. 8 of 2010 and Law No. 9 of 2013, practices on the ground show that there are still gaps in the implementation of regulations that affect the effectiveness of financial institutions in carrying out their supervisory functions. This study aims to analyze the extent to which regulatory gaps affect the performance of financial institutions, as well as to formulate strategies that can be applied to strengthen their authority in dealing with evolving financial crime methods, including through cryptocurrency and financial technology. Using a normative juridical method with a legislative and conceptual approach, data is analyzed from existing regulations, legal literature, and related policies. The results of the analysis indicate that regulatory harmonization, the utilization of supervisory technologies, and enhanced inter-institutional coordination are the main strategies to strengthen the money laundering and terrorism financing prevention system in Indonesia.